Bacterial growth assessment of extraction pliers following tooth extraction in culturing bacterial on various media: a quasi-experimental study - Chairunas, Chairunas; Sinta, Gian Salsabila; Sari, Liza Meutia; Suhanda, Rachmad; Zainul Abidin, Siti Nur Nabihah (Padjadjaran Journal of Dentistry, 2024)
ABSTRACTIntroduction: Tooth extraction injury potentially creating an entry point for bacteria that may cause infection. Dental extraction tools that come into contact with a patient's oral cavity contain many bacteria which can be opportunistic and pathogenic. The purpose of this study was to examine the bacterial growth on tooth extraction pliers following tooth extraction in culturing bacteria on various media. Methods: Type of study is a quasi-experimental research design, using pre and post-test analysis. It was conducted in September–October 2021 at the Teeth and Mouth Dentistry Hospital (RSGM), Universitas Syiah Kuala, focusing on the swab sampling of tooth extraction pliers. The sample examination stage was conducted at the Faculty of Dentistry Laboratory. The study involved culturing bacterial on various media, including NA (Nutrient Agar), MHA (Mueller Hinton Agar), TSA (Triptic Soy Agar), TYS20B (Trypticase Soy-Yeast 20% Sukrose with Bacitracin), and performing gram staining under a microscope. Results: NA media: out of 16 samples cultured, 8 were not covered by bacteria, while the other 8 were. MHA media: all samples were overgrown with bacteria, but each 8 had different characteristics. 9 samples of TYS20B medium were overgrown with bacteria, while the other seven did not show signs of bacterial overgrowth. On TSA media, 5 samples were not overgrown with bacteria, 9 samples were overgrown with bacteria exhibiting solid, yellowish white, and not slimy, and the other 2 samples contained bacteria that were soft, yellowish white, and slimy. Conclusion: Bacillus sp., Diphtheroid basil sp., and Streptococcus mutans were found grown on the agar media.  In general, MHA media is the most effective general growth medium, while TYS20B media is the best media for Streptococcus mutans growth.